The past and future roles of epidemiology and economics in the control of tick-borne diseases of livestock in Africa: The case of theileriosis - Perry, Brian D.; Young, A.S. (Elsevier, 1995)
This paper reviews the past contributions of epidemiology and economics to the control of tick-borne infections of cattle in Africa. The factors affecting successful and unsuccessful control are evaluated on a gographical and on a production systems basis, with particular reference to Theileria parva infection. The paper then discusses four areas of the emerging disciplines of epidemiology and economics which are likely to play an important role in better control of tick-borne diseases in the future, and illustrates their potential contributions. The four areas are: predicting target populations for vaccines through the use of serological tests, determining the appropriate sampling strategy to quantify tick-borne infection prevalence, modelling distributions and dynamics of tick-borne infections and predicting the economic impact of tick-borne diseases and their control.